Germination studies of Ganoderma boninense spores from oil palms in Malaysia - Ho, Yin Wan; Nawawi, A. (Universiti Pertanian Malaysia, 1986)
Spores of Ganoderma boninense obtained from sporulating sporophores attached to infected oil palms or infected cut stumps, germinated readily but spores which were squeezed out from detached sporophores did not. None of the spores germinated during the first 24 hrs of incubation but by 30 hrs, 31.5- 64% of the spores germinated on various media. The most suitable medium for germination was lima bean agar followed by corn meal agar and rice dextrose agar. Spore germination was poor on Czapeks agar. Warmer temperatures of 25-- 31°C were more/favorable to germination than cooler temperatures of21 - 23°C.